1964
DOI: 10.1246/bcsj.37.117
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Transient Intermediates in the Photoreduction of Methylene Blue

Abstract: The intermediate species which are produced in the course of the photoreduction of methylene blue have been investigated by flash photolysis in plain aqueous, borate and phosphate buffer solutions with and without reducing agents. In an acidic solution, an absorption band with the lifetime of 30μsec. appears at 375 mμ, while in neutral and basic solutions, two bands appear, at 415 and 520 mμ, with lifetimes of 70∼90 μsec. The bands at 375 and 415 mμ are considered to be due, respectively, to the acidic and bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

1968
1968
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(25 citation statements)
references
References 6 publications
4
21
0
Order By: Relevance
“…2 The results of the present ODMR and EPR studies on the compound in a durene host indicate that the molecule is likely to be planar in the Tl state in durene. The energies of the 3nr* and 'nr* states of the bimane in the neat crystal and in a durene host crystal probably represent those of planar excited states.…”
Section: (1968)mentioning
confidence: 66%
“…2 The results of the present ODMR and EPR studies on the compound in a durene host indicate that the molecule is likely to be planar in the Tl state in durene. The energies of the 3nr* and 'nr* states of the bimane in the neat crystal and in a durene host crystal probably represent those of planar excited states.…”
Section: (1968)mentioning
confidence: 66%
“…Demethylation is known to occur for methylene blue and toluidine blue 0 by photoreduction (17,18). It has also been reported that demethylation of methylene blue occurs under basic conditions (19,20); however, the dye was stable below pH 9.5.…”
Section: Resultsmentioning
confidence: 96%
“…This leuco form can be oxidised back to MB by atmospheric oxygen, although this reaction is not quantitative and is accompanied by a slight permanent degradation of the dye. A number of different reaction mechanisms have been proposed for the photoreduction of methylene blue [16][17][18]. Kato et al [16] proposed that the semi-reduced species was generated by the reaction with the excited monomer triplet with the ground state monomer.…”
Section: Mbmentioning
confidence: 99%
“…A number of different reaction mechanisms have been proposed for the photoreduction of methylene blue [16][17][18]. Kato et al [16] proposed that the semi-reduced species was generated by the reaction with the excited monomer triplet with the ground state monomer. Danziger et al [17] presented a scheme based on the irradiation of MB monomer or dimer, resulting in the formation of a dimeric charge transfer species, leading to the formation of leuco MB (MBH) or regeneration of the ground state.…”
Section: Mbmentioning
confidence: 99%